Averting the Apocalypse social movements in India today - Bonner, Arthur (Duke University Press, 1990)
A Longing for Freedom -- A Missed Tryst -- The Rich and the Poor -- We, the Invisible -- The Rescue of Bishnu and Uma -- Sister Rita's Report -- Devadasis and Hijras -- Female Feticide -- The Goddess of Food -- Tribal India -- A Truck and Some Cows -- Creating a New Revolutionary Class -- The Mutiny of the Innocents -- Save the Western Ghats -- The Wandering Charcoal Makers -- The Failure of Charisma -- The Golana Massacre -- Temples and Toilets -- A Museum of Living Fossils -- Temples or Tombs? -- Pragmatic Activists -- Population and Sterilization -- A Model for Community Health -- Working for Women -- Slaves of Sabarmati -- The Rape of Guntaben -- The Mystic Dancer -- Bihar: Blindings and Massacres -- The Role of Activists -- Nonviolent Melodrama -- Journalism and Its Perils -- We Have a Dream -- Myths and Identity -- The Front Paw of the Revolution -- From Revolt to Renewal -- A Civilization That Doesn't Work -- Death by Encounter -- A Village Confrontation -- A Man with Faith in India -- Broken Promises, Broken Children -- The Little Carpet Makers -- The Little Match Girls -- Riddles of Hinduism -- The Conversions at Meenakshipuram -- Manipulating Myths and Symbols -- The Juggernaut Claims Its Victims -- The Politics of Passion -- The Fiery Swami -- The Triumph of Gandhi's Assassin -- Averting the Apocalypse